TRIM29 prevents hepatocellular carcinoma progression by inhibiting Wnt/β-catenin signaling pathway. (19th December 2018) - Xu, Mingxing; Hu, Jingxiong; Zhou, Boxuan; Zhong, Yuesi; Lin, Nan; Xu, Ruiyun
Abstract: TRIM29 plays an important role in many neoplasms. In this study, we aimed to elucidate its role in hepatocellular carcinoma (HCC) and explore the corresponding potential mechanism. The expression level of TRIM29 in HCC samples and hepatoma cell lines was detected. We found that TRIM29 was down-regulated in clinical HCC samples and cultured hepatoma cell lines by western blot analysis and quantitative polymerase chain reaction. In addition, we demonstrated that higher TRIM29 expression was associated with higher differentiation grade of HCC. To explore the effect of TRIM29 on hepatoma cells and its possible mechanisms, TRIM29-knockdown and overexpression cell models were constructed. The results showed that the depletion of TRIM29 promoted liver cancer cell proliferation, clone formation, migration and invasion in vitro probably through the Wnt/β-catenin signaling pathway. This study revealed the inhibitory roles of TRIM29 in HCC and the possible mechanisms.